Recent Advances in IoT Security for Real-Time Data Integration - Abdul Hameed Mohammed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This article examines the latest advancements in IoT security, focusing on protecting real-time data in distributed networks. The article explores how emerging technologies like blockchain, zero-trust architecture, and machine learning are addressing critical security challenges in IoT ecosystems. The article analyzes the evolution of security threats and solutions across various sectors, including healthcare, manufacturing, and financial services. Special attention is given to the integration of advanced security frameworks that balance robust protection with operational efficiency. The article also investigates industry-specific implementations and their effectiveness in addressing unique security requirements while maintaining performance standards. Finally, the article looks ahead to future directions in IoT security, including quantum-ready security measures, edge computing security, and automated security operations.